G455(P) Psychological sequelae in obese paediatric patients and predictors for weight loss. (27th April 2016) - Gallen, H; Banerjee, I; Clayton, PE; Ehtisham, S; Nicholson, J; Padidela, R; Patel, L; Tobin, H; Salsbury, L; Skae, M
Abstract : Aims: There is limited data on the psychological sequelae of obesity in paediatric patients. We aimed to assess the prevalence of psychological comorbidities in obese paediatric patients and to explore whether patient and parent motivation scores can be used as a predictor for weight loss. Methods: Internationally validated self-report questionnaires were offered to 19 patients and their parents from a tier 3 paediatric obesity clinic. These included the Paediatric Index of Emotional Distress (PI-ED); Beck Youth Inventory™ exploring self-perceptions of competency, potency and self-worth; Paediatric Quality of Life Inventory (PaedsQL™); Parent-Proxy report (PaedsQL™Parent) and two in-house derived motivation questionnaires for parents and patients. Results: 14 patients completed the PI-ED, of which more than half (57%) reported emotional distress (5=female, 3=male). 15 patients completed the Beck Youth Inventory™ of which 53% reported low self-esteem (4=female, 4=male). 17 patients completed QoL scores and scored on average below normal cut offs for the social and physical domains, as well as for overall psychosocial health and overall QoL (total score). The parents of these children also reported below normal cut offs for all domains except schooling. Those aged <10 years reported the highest QoL scores. Females reported significantly lower scores for emotional, social and overall QoL domains, particularly those between 10–15.9 years. 18 children and 19 parents completed motivation scores. All of those reported medium to high motivation with a non-significant correlation between reduction in BMI SDS (z-score) and increased patient and parent motivation scores (p = 0.19 and p = 0.47 respectively). Discussion/Conclusion: More than half of obese paediatric patients in our cohort experience a high prevalence of emotional distress and low self-esteem. Obese paediatric patients are at risk of experiencing reduced QoL. Females between the ages of 10–15.9 years are the most vulnerable to experiencing psychological comorbidities within this cohort. Initial observations may suggest high motivation scores are a positive indicator for weight change but more research should be carried out to establish a link.